“Gromming”: el minotauro en internet. El derecho penal del enemigo frente al pederasta de la era digital - Granja, Pedro Javier (Derecho penal y criminología, 2020)
Approximately, 2.3 billion people connect to the internet in today’s world, with increasingly anonymous contacts. The largest users percentage are digital natives, that means, human beings who grew up in the middle of the network society. We refer to children and adolescents, which has caused the pedophile of the last century to transfer his field of action to a field that presents immeasurable difficulties identifying and neutralizing the problem. The digital Minotaur lurks, its voracity does not stop, it associates in international networks, it uses technology to circumvent controls. It contacts children under various disguises, prepares them to satisfy its sexual desires in a terrifying ritual of emotional manipulation that generally ends in blackmail of the minor and subsequent sexual abuse. Grooming, in many current legislations, presents serious deficiencies regarding its typification. In this work we present a study from the coordinates of systemic normativism, presenting some ideas to go deeper into the discussion and contribute to the fight against these criminals.